PERSEPSI PENGUSAHA KERIPIK TEMPE SANAN TERHADAP PEMBIAYAAN BANK SYARIAH (STUDI INDUSTRI TEMPE SANAN KOTA MALANG) - Viana, Vira Okta; Zuhroh, Idah; Suliswanto, Muhammad Sri Wahyudi (Journal of Financial Economics & Investment, 2022)
This study aims to describe the micro business profile of Sanan tempe chips and provide an overview of the perceptions of Sanan tempe chips entrepreneurs on Islamic bank financing. The analytical method used is descriptive analysis research method by combining qualitative and quantitative method approaches in the different stages of the research process. The results showed that the profile of tempe chips entrepreneurs in terms of production could produce between 800-2,800 per month on average with a price of Rp. 7000, with an average income between 1,000,000 – 5,000,000 with a percentage of 48.6%. For the marketing aspect, it uses more inside and outside the region, marketing outside the region such as: Batu City, Pasuruan, and Surabaya.  The perception of the tempe sanan chip entrepreneur on financing, in terms of 4 aspects: in 4 aspects it has a different percentage level and criteria. The criteria that are lacking are in the procedural aspect with a percentage rate of 59% of respondents compared to the other 3 aspects. This shows that there are many responses that choose less appropriate regarding the disbursement of financing and the financing application process.